Biological response to dissolved versus dispersed oil. (January 2020) - Bera, Gopal; Doyle, Shawn; Passow, Uta; Kamalanathan, Manoj; Wade, Terry L.; Sylvan, Jason B.; Sericano, Jose L.; Gold, Gerardo; Quigg, Antonietta; Knap, Anthony H.
Abstract: The water-soluble compounds of oil (e.g. low molecular weight PAHs) dissolve as a function of their physicochemical properties and environmental conditions, while the non-soluble compounds exist as dispersed droplets. Both the chemical and physical form of oil will affect the biological response. We present data from a mesocosm study comparing the microbial response to the water-soluble fraction (WSF), versus a water-accommodated fraction of oil (WAF), which contains both dispersed and dissolved oil components. WAF and WSF contained similar concentrations of low molecular weight PAHs, but concentrations of 4- and 5-ring PAHs were higher in WAF compared to WSF. Microbial communities were significantly different between WSF and WAF treatments, primary productivity was reduced more in WSF than in WAF, and concentrations of transparent exopolymeric particles were highest in WSF and lowest in the controls. These differences highlight the importance of dosing strategy for mesocosm and toxicity tests. Highlights: PAHs availability differed in water soluble (WSF) vs. water accommodated (WAF) oil fractions. Microbial communities differed between WSF and WAF treatments. Half-Lives of 3–5 ring PAHs were longer in WSF compared to WAF treatments. Primary productivity was more impaired in WSF than in WAF treatments. TEP production was higher in WSF than in WAF, and both higher than in Controls.